The Legal Regime of the Secondary Modalities of Constitution of the Real Right of Superficies - Costache, Mirela; Cornea, Valentina; Mirica, Stefania (Acta Universitatis Danubius. Juridica, 2022)
The law problem analysed in this paper regards the atypical situation of the constitution of the real right of superficies, which is materialised in the fact that, in the last paragraph of the article 693 of the Romanian Civil Code there are stipulated two special cases in which this right can be formed. The first one refers to the inscription of the superficies right in the favour of the one that built on the land of someone else, based on the decision of the landowner to give up the right to invoke the accession. The second one presumes the cession in favour of a third party of the right to invoke the accession. Therefore, the new legal framework capitalizes on both previous doctrinal experience and similar provisions of the Quebec Civil Code and includes in the sphere of possibilities of acquiring the right of superficies either a potential right of renunciation or the cession of this right in favour of another party. However, the two situations rise difficulties either by the legal nature of the act of renunciation or by the way the cession is born. This paper analyses the enumerated situations and contains personal opinions in this matter.